2018
DOI: 10.1016/j.bbrep.2018.08.005
|View full text |Cite|
|
Sign up to set email alerts
|

Insulin down-regulates cardioprotective SUR2A in the heart-derived H9c2 cells: A possible explanation for some adverse effects of insulin therapy

Abstract: Some recent studies associated insulin therapy with negative cardiovascular events and shorter lifespan. SUR2A, a KATP channel subunit, regulate cardioprotection and cardiac ageing. Here, we have tested whether glucose and insulin regulate expression of SUR2A/KATP channel subunits and resistance to metabolic stress in heart H9c2 cells. Absence of glucose in culture media decreased SUR2A mRNA, while mRNAs of Kir6.2, Kir6.1, SUR1 and IES SUR2B were increased. 2-deoxyglucose (50 mM) decreased mRNAs of SUR2A, SUR2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…Mitochondrial ATP‐sensitive K + channel in the mitochondrial inner membrane is involved in cardioprotective pathways to against heart diseases including I/R injury. Several studies suggest that sulfonylurea receptor 2A which serves as a subunit of ATP‐sensitive K + channel is involved in regulation of myocardial resistance to metabolic and oxidative stress and IES SUR2B is a possible part of mitochondrial ATP‐sensitive K+ channel mediating cardioprotection . On the other hand, VDAC is another important channel on the outer mitochondrial membrane .…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial ATP‐sensitive K + channel in the mitochondrial inner membrane is involved in cardioprotective pathways to against heart diseases including I/R injury. Several studies suggest that sulfonylurea receptor 2A which serves as a subunit of ATP‐sensitive K + channel is involved in regulation of myocardial resistance to metabolic and oxidative stress and IES SUR2B is a possible part of mitochondrial ATP‐sensitive K+ channel mediating cardioprotection . On the other hand, VDAC is another important channel on the outer mitochondrial membrane .…”
Section: Discussionmentioning
confidence: 99%
“…While ischemic heart disease is the leading cause of morbidity and mortality [17], it does not per se explain the preservation of K ATP channels through evolution [7]. We have previously shown that and increase in SUR2A and consequent increase in K ATP channel levels increase physical endurance and prolong lifespan [15,22] while decreased SUR2A levels decrease cellular resistance to metabolic stress [5]. However, no connection between cardiac electrophysiology and improved adaptation to physical stress in mice overexpressing SUR2A has been made so far.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in intracellular SUR2A level increases levels of fully assembled K ATP channels, which, in turn, confers cardioprotection [5]. On the other hand, a decrease in SUR2A levels results in increased cardiac susceptibility to metabolic stress [6]. As pyrazinamide affects NAD and NADH levels, it could affect the level of SUR2A as well.…”
mentioning
confidence: 99%